Association of infant and maternal serum 25-hydroxy vitamin d levels with severity of pneumonia in infants - Katoch, Gaurav; Sharma, Seema; Sharma, Milap; Gunjiganvi, Anand; Singhal, Amrita (International Journal of Contemporary Pediatrics, 2016)
Background: Vitamin D is a prohormone essential for normal absorption of calcium from the gut. Solar UVB radiations transform pre-vitamin D in the skin to vitamin D3. The aim was to find out association of infant and maternal serum 25 (OH) D levels with severity of pneumonia in infants. Methods: In this prospective cross sectional study conducted in a tertiary care centre of Northern India during 2014-2015, a total of 160 subjects were enrolled; the study group involved infants with pneumonia of varying severity and their mothers while normal infants and their mothers were included in control arm of the study. This was followed by quantitative estimation of 25 (OH) D3 of all the enrolled infants along with their mothers. Results:Among 40 infants presenting with variable severity of ARI taken as cases, the median 25 (OH) D levels was 12.55 ng/ml and 40 healthy infants taken as controls was 12.70 ng/ml. The median 25 (OH) D levels of mothers of infants enrolled as cases and controls were 13.00 ng/ml and 11.15 ng/ml respectively. The observations showed vitamin D deficiency in majority (78.75%) of our studied subjects although we could not find any statistically significant difference between the study group and control group. Conclusions: This study showed vitamin D deficiency in both the studied groups although there was no causal relation between the vitamin D levels and severity of pneumonia. This study also showed that vitamin D levels were not statistically significant in infants presenting with variable severity of ARI and healthy infants. The observations of the study indicate that vitamin D deficiency is prevalent in high risk population group in Himachal Pradesh.